Recent biopharmaceutical studies on the evolution of ophthalmic drugs - Cima, Luiza-Madalina; Neculai, Ana-Maria (Eximia, 2022)
Ophthalmic pharmaceuticals have been one of the most important and widely developed fields of pharmaceutical technology for decades. The main reason for the continued interest of scientists in these forms of medicine is the issue of low bioavailability of the drug after application to the eyeball. The broad classification of ocular drug administration results in two categories: drugs concerned with anterior segment of the eye and drugs concerned with posterior segments of the eye. About 90% of ophthalmic formulations on the market are available in the form of eye drops and the sites of action are for diseases that occur in the anterior segment of the eye. For the release of ophthalmic drugs, the posterior segment of the eye is often a choice of interest to locate the drug, using new approaches. In this regard, this article highlights new developments in ophthalmic pharmaceutical formulations, such as in situ gel formulation, nanoparticles, liposomes, nanosuspension, microemulsion, eye inserts and so on and their progress to overcome problems associated with conventional dosage forms and also to improve bioavailability as well as support the release of the drug at the target site.